Mindfulness, Quality of Life, and Resilience among Mothers of Children with ASD: The Mediating Role of Cognitive Emotion Regulation Strategies - Abdul Azeem Mubarak, Doaa Mohammed (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: The aim is to investigate the relationships between mindfulness, QoL, and resilience based on the mediating role of Cognitive Emotion Regulation strategies (CERs) data on 110 mothers were collected and analyzed. Methods: A descriptive research with a correlational model in which the path analysis model is used to obtain the relationship between variables was used. Results indicate that Adaptive CER has a direct and significant correlation with QoL, Mindfulness, and Resilience. Non-Adaptive CER has an inverse and significant correlation with QoL, Mindfulness, and Resilience. Results: The results of structural equation modeling indicate that all paths adaptive CERs and non-Adaptive CERs were significant. E.g. the path of mindfulness to adaptive CERs was significant, and to non-adaptive CERs was significant. The path of QoL to adaptive CERs was significant, and to non-Adaptive CERs was significant. The path of resilience to adaptive CERs was significant, and to non-Adaptive CERs was significant. Conclusion: It can be said that when the mother has mental health components, she can provide a rich and healthy environment for the child with ASD to be able to help him/her develop.